Validating the Cognitive Scale for Down Syndrome (CS-DS) to Detect Longitudinal Cognitive Decline in Adults With Down Syndrome - Startin, Carla M.; Lowe, Bryony; Hamburg, Sarah; Hithersay, Rosalyn; Strydom, Andre; , LonDownS Consortium; Fisher, Elizabeth; Nizetic, Dean; Hardy, John; Tybulewicz, Victor; Karmiloff-Smith, Annette (Frontiers in Psychiatry, 2019)
Down syndrome (DS) is associated with intellectual disability and an ultra-high risk of developing dementia. Informant ratings are invaluable to assess abilities and related changes in adults with DS, particularly for those with more severe intellectual disabilities and/or cognitive decline. We previously developed the informant rated Cognitive Scale for Down Syndrome (CS-DS) to measure everyday cognitive abilities across memory, executive function, and language domains in adults with DS, finding CS-DS scores are a valid measure of general abilities, and are significantly lower for those with noticeable cognitive decline compared to those without decline. To further test the validity of the CS-DS in detecting changes associated with cognitive decline we collected longitudinal data across two time points, approximately 1.5-2 years apart, for 48 adults with DS aged 36 years and over. CS-DS total scores (78.83±23.85 vs 73.83±25.35, p=0.042) and executive function scores (46.40±13.59 vs 43.54±13.60, p=0.048) significantly decreased between the two time points, with scores in the memory domain trending towards a significant decrease (22.19±8.03 vs 20.81±8.63, p=0.064). Adults with noticeable cognitive decline at follow-up showed a trend to significantly greater change in total scores (7.81±16.41 vs 3.59±16.79, p=0.067) and significantly greater change in executive function scores (5.13±9.22 vs 1.72±9.97, p=0.028) compared to those without decline. Change in total scores showed significant correlations with change in scores from other informant measures of everyday adaptive abilities and symptoms associated with dementia, and participant assessment of general cognitive abilities (all p<0.005), while change in memory scores (R2=0.28, p=0.001) better predicted change in participant cognitive assessment scores than change in executive function (R2=0.15, p=0.016) or language (R2=0.15, p=0.018) scores. These results suggest informants may better detect changes in the executive function domain, while change in informant rated memory scores best predicts change in assessed cognitive ability. Alternatively, memory domain scores may be sensitive to changes across both early and late cognitive decline, whereas executive function domain scores are more sensitive to changes associated with later noticeable cognitive decline. Our results provide further support for the validity of the CS-DS to assess everyday cognitive abilities and to detect associated longitudinal changes in individuals with DS.